Apolipoprotein E gene, environmental risk factors, and their interactions in dementia among seniors. (17th December 2012) - Meng, Xiangfei; D'Arcy, Carl
Abstract : Objectives: Little research has been conducted to explore the joint effect of apolipoprotein E (ApoE) genotypes and environmental risk factors on dementia. In this study, we examined the roles of ApoE alleles and genotypes in dementia and cognitively impaired not demented (CIND), assessed the risk of co‐existing or prior health conditions (i.e. depression), family history of diseases, and lifestyle factors on dementia, and explored the interactions between genetic and environmental risk factors and their joint effects on dementia and cognitive impairment. Methods: This is a genetic association study. A total of 1185 seniors (391 dementia, 389 CIND, and 405 cognitively intact, matched for age and gender) were selected from the Canadian Study of Health and Aging clinical assessment datasets. Multivariate logistic regression was used to explore the association between ApoE, environment risk factors, and outcomes. Results: Participants with ApoE ε4 alleles or ε3/ε4 genotypes were at risk of dementia. More education reduced the risk of dementia or CIND. Previous health conditions (e.g. stroke) increased the risk of dementia or CIND. Regular exercise decreased the risk of CIND. ApoE ε3/ε4 genotype and baseline depression had a 7.97‐fold greater risk of incident dementia after adjusting for other significant risk factors. No interactions were found in any dementia and CIND models. Conclusions: More attention should be paid to assess and treat depressed older people, especially for those with ApoE ε3/ε4 genotypes. Further replication studies in different populations are warranted. Copyright © 2012 John Wiley & Sons, Ltd.